Is tilapia farming financially profitable and efficient? Policy options for sustainable farming: Policy options for sustainable tilapia farming (Journal of the Bangladesh Agricultural University, 2019)
Tilapia (Oreochromis niloticus) is known as ‘fish for the poor’ due to its low market price. However, the question remains about the sustainability of this species because of high production cost and lower market price.  Therefore, this study examined the financial profitability, technical efficiency and tried to find out the policy options for increasing the financial benefit of fish farmers. A total of 250 tilapia fish farmers were selected from seven tilapia producing areas of Bangladesh. To fulfill the objectives of this study, profitability, stochastic frontier production function, and sensitivity analysis were employed.  Considering all selected farmers, tilapia farming found a profitable business where undiscounted BCR was only1.11. Among all cost items, only feed consists of 70 percent of the total production cost.  The mean technical efficiency level of tilapia fish farmers was 85 percent, implies that by operating at full technical efficiency levels, tilapia yield could be increased from the current level of 20.98 to 24.13 tons per hectare and efficient farmers found more productive than inefficient farmers. Farmer’s financial benefit can be increased by reducing the feed price, decreasing FCR or increasing the output price. Feed price reduction or enhance the quality of feed could be effective policy options for sustaining the tilapia farming.J. Bangladesh Agril. Univ. 17(1): 92–98, March 2019